Analisi Kualitas dan Uji Organoleptik Abon Sapi Terhadap Penambahan Buah Keluwih (Arctocarpus communis) - M. Nasir (Agricultural Faculty, 2007)
ABSTRACT. A study on the effect of addition of kuluwih on quality and organoleptic test of abon sapi conducted at meat and fish processing loboratory and livestock food laboratory of animal husbandry department faculty of agriculture of syiah kuala university, in august 2006. The research design was completely randomized design that consists of 5 treatments with 4 replications. The treatments were; A = 100 % abon sapi; B=abon sapi and 5 % keluwih; C= Abon sapi and 10% keluwih; D = Abon sapi and 15% keluwih; and E= Abon sapi and 20% keluwih. The results showed that there were no significant effect of addition keluwih on abon sapi on quality and organoliptic test. There was also no significant effect of addition keluwih on rot test that the ammoniac yield was relatively low so that the abon sapi was safely consumption.